암살 = Assassination - Chʻoe, Tong-hun; Yi, Ki-ch'ŏl (Caper Film, Showbox, 2015)
While Korea is occupied by the Japanese Army in 1933, the resistance plans to kill the Japanese Commander. But their plan is threatened by a traitor within their group and also the enemies' forces are hunting them down.https://www.worldcat.org/title/amsal/oclc/1013425539&referer=brief